Changes in the governance of the reading subject: Swedish reading policy, c.1949-1984 - Lindsköld, Linnéa; Hedemark, Åse (International journal of cultural policy : CP, 2024)
This paper analyses significant changes in the political rationality underpinning Sweden's official reading policy between the 1940s and 1980s. Using official inquiry reports as empirical material and drawing on a discourse analytical method, we examine policy changes regarding ideal readers (what reading should result in) and administrative practices (what policy actions could be used) and the kinds of academic knowledge that was used to justify specific measures. It is found that official reading policy ceased to be limited to distributing literature and expanded to include active reading promotion. The replacement of sociological perspectives by cognitive viewpoints as constituting knowledge is also noted. It is concluded that changes in the political rationality had consequences for how the individual reader was construed, from a subject with the potential to change society to a subject who had to adjust to society. We argue that the cultivation of readers evident in reading policy constitutes a specific technique of governance not sufficiently considered in previous cultural policy research.